PERAN NOTARIS DALAM PEMBUATAN AKTA IZIN ROYA HAK TANGGUNGAN KARENA HAPUSNYA HUTANG DALAM PERSPEKTIF KEPASTIAN HUKUM - EFTY HINDARU SUDIBYO; Amin Purnawan (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2017)
Making of license process of roya mortgage right need the role of notary. The research Notary's role in the making of license deed of roya mortgage right because the debt elimination in perspective of legal certainty. The problem in this research are 1) how did the process of making Permit Roya Deed Rights due to debt removal, 2) notary role in making deed of Permit Roya Mortgage Rights due to the elimination of Debt in perspective of legal certainty and 3) what are the Constraints and solutions in the role of notary in making the deed of Roya mortgage right due to the elimination of Debt in the perspective of legal certainty.Approach method used is juridical empirical method, juridical research with the object in the form of law, empirical research is the existence or results of research on the pouring of the applicable laws in the community.The result of this research is that the process of making Deed of Roya mortgage right due to debt removal is based on requests from interested parties and deletion based on the decision of the District Court. The role of a notary in the making of the deed of Roya mortgage right because of the elimination of Debt in the perspective of legal certainty is that roya can be processed if all the requirements are complete. One of them is Roya Letter. The problem is if the roya letter is lost or the certificate of mortgage is lost then the roya process can not be executed by the National Land Agency, then in this case the notary can help with the record in accordance with the rules of notary can issue or make Roya Permit or can be called as a roya concentrate in the form Notarial deed prior to the preparation of a loss report from the police to be issued a certificate of loss. The constraints of the notary's role in the making of the deed of Roya Hak Liability due to the elimination of Debt in the perspective of legal certainty are Roya period exceeds seven days from the date of application, Roya costs exceeds the provisions, Roya Partial Objects of Mortgage Rights which are Not Consist of Multiple Rights to Land and Completeness Roya Requirements Not Fulfilled. While the Solution to overcome the constraints in the role of notary in making the deed of Permit Roya mortgage right due to the elimination of Debt in the perspective of legal certainty is the Accuracy of Time In Roya Settlement Completion Settlement, Roya Rights Cost Assurance and Completeness of Roya Key words; Notary, Roya, Mortgage Right